Analysis of South Africa’s non-fuel mineral exploration expenditure to assess investment climate in the mining industry in the post-apartheid era - Mulaudzi, Masala (My University, 2021)
The research analysed the impact of the Minerals and Mining Policy of 1998 as a document that laid the philosophy and the foundation of the role of the mining industry in the South African economy in the new democratic dispensation. This document sought to transform the industry to include the participation of the previously disadvantaged people due to apartheid policies and the goal was to be achieved with minimal disruption to investment and sustainability in the industry. The Mineral and Petroleum Resources Development Act 28 of 2004 (MPRDA) underpins the legislative framework to realise the aspirations expressed in the mineral policy. Two decades have passed since the publication of the Minerals and Mining Policy in 1998 and the mining industry has gone through fundamental changes both locally and internationally. Both the Minerals Policy and the ensuing legislations were analysed to gauge how responsive they have been to the changing environment in terms of sustainability of the South African mining industry. This was examined through the integration of exploration expenditure, discovery of new deposits or mines, and production output of gold, platinum, copper and diamond in the past two decades. The purpose of this research was to identify shortcomings of the current mining sector regulatory environment that has led to a shrinkage in investment, especially greenfields exploration, in the in South African mining industry. The research results illustrate that despite South Africa’s massive mineral endowment, exploration investment expenditure and production output in the mining industry has continued declining in the past two decades. It is postulated that the shift in post-apartheid mineral regulation and legislation was intended mainly to dismantle apartheid injustices and policies with less effort devoted to growing and sustaining an industry that is in decline. As a consequence, South Africa has failed to deploy the right policy instruments to stimulate mineral development and attracting investment to improve the lives of the people on the back of the massively rich mineral endowment
A research report submitted to the Faculty of Engineering and the Built Environment, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Mining Engineering, 2021